PakSurg: The first trainee-lead model for multicenter surgical research collaboration in Pakistan - Waqar, Usama; Shaheer Ahmed; Ronika Devi Ukrani; Maheen Mansoor; Sadaf Khan; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
We describe creation and piloting of the PakSurg Collaborative, devised via integration of existing traineeled collaborative models in the United Kingdom with the resource-limited surgical care in Pakistan. This is the first trainee-lead surgical research collaborative in Pakistan, established by the student-lead Surgery Interest Group from the Aga Khan University. The project involved creation of a model that included a steering committee comprising of five teams which worked in conjunction with collaborators from multiple hospitals. To facilitate this collaboration, a comprehensive and cost-efficient study management pathway was developed. The PakSurg Collaborative has the potential to deliver methodologically robust, high-quality, multicenter surgical evidence from Pakistan. This nationally representative data could inform evidence-based surgical guidelines, potentially translating into improved outcomes for patients undergoing surgery. Continuous...